The appropriacy and applicability of English assessment against CEFR global scale: teachers’ judgement - Nurul Farehah Mohamad Uri; Mohd Sallehhudin Abd Aziz (Penerbit Universiti Kebangsaan Malaysia, 2020)
This study intends to identify the appropriateness of the writing and reading assessment items of the current English syllabus according to the targeted CEFR levels set by the Ministry of Education and to find out English teachers’ familiarity with CEFR writing and reading scales by suggesting suitable CEFR levels for writing and reading assessment items. An assessment checklist was used to collect the data involving 331 secondary school English teachers. Results show that most of the assessment items are found to be suitable and applicable to be used in the CEFR. This study also proves that the teachers were aware of the six levels of CEFR global scale because they were able to identify the suitable CEFR level that matches against CEFR target level set by the Ministry of Education. In conclusion, the Ministry of Education, Malaysia should consider to continue using some part of the current English syllabus and assessment instead of recommending its total abolishment.